[5]Helicene-based chiral triarylboranes with large luminescence dissymmetry factors over a 10−2 level: synthesis and design strategy via isomeric tuning of steric substitutions. Issue 16 (1st April 2022) - Zhao, Fei; Zhao, Jingyi; Wang, Yu; Liu, Hou-Ting; Shang, Qinghai; Wang, Nan; Yin, Xiaodong; Zheng, Xiaoyan; Chen, Pangkuan
Abstract : We have proposed a molecular design strategy to achieve high-performance CPL-active materials with a considerably large g lum > 1.2 × 10 −2 via tuning of organoborane chemistry and isomeric substitutions with tunable steric effects. Abstract : Constructing chiral luminescent systems with both large luminescence dissymmetry factor ( g lum ) and high luminous efficiency has been considered a great challenge. We herein describe a highly efficient approach to sterically stabilize the helical configurations of carbo[5]helicenes for improved CPL properties in a series of π-donor and π-acceptor substituted [5]helicenes (1, 2, 3, 4 and 5 ). Enabled by the ortho -installation of methyl groups as well as the steric effects of triarylamine (Ar3 N) and triarylborane (Ar3 B) handles in meta -substituted [5]helicenes, their optical resolution into enantiomers has been accomplished using preparative chiral HPLC. The molecular chirality of [5]helicenes can be transferred to Ar3 B and Ar3 N as light emitters, which allowed further investigations of their chiroptics, including optical rotation, circular dichroism (CD) and circularly polarized luminescence (CPL). Remarkably, 4 has been demonstrated to display dramatically enhanced CPL performance with a much larger g lum (>1.2 × 10 −2 ) and an increased emission quantum efficiency ( Φ S = 0.75) compared with the other analogues, as a result of the isomeric tuning of substitutions with differential steric and electronic effects. These experimentally observed CPL activities were rationalized by TD-DFT computations for the angle ( θ μ, m ) between electric and magnetic transition dipole moments in the excited states. In addition, the conspicuous intramolecular donor–acceptor charge transfer led to thermal responses in the emissions of 2 and 4 over a broad temperature range.